A comprehensive review on phytochemical, pharmacological and therapeutic properties of Agrimonia eupatoria L. - Mozhgan Ghobadi Pour; Naser Mirazi; Shirin Moradkhani; Mahmoud Rafieian-kopaei; Mohammad Rahimi-Madiseh (Shahrekord University of Medical Sciences, 2021)
Agrimonia eupatoria is a perennial herb belonging to the Rosaceae family that all its parts are used to treat various diseases. In this article, we aimed to present a comprehensive review on the phytochemical, pharmacological, and therapeutic effects of this plant. We searched various databases and summarized the data documented in literature from 1976 to 2020. Agrimonia eupatoria has effects on various kinds of cancer, oxidative stress, diabetes mellitus, hepatitis B, and liver damage. It also has anti-adhesive, antibacterial, antimicrobial, and wound healing properties. It induces nitric oxide and inhibits pro-inflammatory cytokines production. Phytochemical studies related to this plant has led to isolation and identification of tannins, coumarins, and flavonoids as the most active chemicals with biological effects. Based on this comprehensive review about Agrimonia eupatoria, there will be more opportunities for investigators to search and discover ways to use bioactive agents of this herb to develop new Agrimony based medicines.